The Art of Protest : Culture and Activism from the Civil Rights Movement to the Streets of Seattle - Reed, T. V. (Thomas Vernon) (Book collections on Project MUSE., 2005)
Impact the above-mentioned movements, as well as the dramatic displays of the Black Panthers, the poetry of the Women's Rights Movement, Chicano movements and the revolutionary mural, the American Indian Movement in film, rock music approaches to African famine and apartheid, the graphic arts of ACT UP, and the discourse of environmentalism. Annotation 2006 Book News, Inc., Portland, OR (booknews.com).